(untitled) (Delta Medical College Journal, 2017)
Background: Early childhood care plays an important role in childrens development and provides a valuable support to young children. High quality child care can have a positive influence on childrens development. Objective: To find out the child care practices among the mothers of below five year children in a semi urban area of Bangladesh and to find its association with some important demographic variables. Materials and method: This descriptive type of cross-sectional study was conducted among 440 respondents who were selected purposively at Purba Chandra, Shafipur Upazilla, Gazipur in Bangladesh in January, 2016. A pre-designed semi structured questionnaire was used to collect data by face to face interview. Results: Majority of the respondents (72.05%) were within the age group of 16-25 years. About 25% (111) children were within 0-12 months of age. Among the respondents 280 (63.64%) were housewives and 141 (32.05%) were garment workers. Maximum mother (72.73%) herself took care of their children and only 86 (19.54%) were cared by their grandmother/father. Majority of the children (87.05%) took colostrum as their first food, 164 (37.27%) children were breast fed up to age of 13-24 months and 302 (68.64%) children received exclusive breast feeding up to 6 months. Most of the children (92.95%) were vaccinated as per EPI schedule. Among them 283 (64.32%) children suffered from disease in last 3 months and 225 (79.51%) took treatment for their illness. Among them 83 (36.89%) took treatment from quack and only 76 (33.78%) children took treatment from private doctor. Conclusion: In this study, most of the mothers did not complete their secondary education and had a lack of knowledge of child rearing practice. This study provided a vivid picture of the child care practice among mothers and could help to the concerned authority in their policy making and planning to alleviate the problem. Delta Med Col J. Jul 2017 5(2): 76-82